RESTORATIVE JUSTICE AND HUMAN RIGHTS ISSUES IN ADOPTING ALTERNATIVE DISPUTE RESOLUTION PLATFORMS TO SETTLE CRIMINAL MATTERS IN NIGERIA - Imenger, Emmanuel T.; Oyebode, Musibau Olabamiji (African Journal of Social and Behavioural Sciences, 2024)
The Criminal Justice System (CJS) is commonly known for its retributive and rehabilitative mindset of punishing offenders, according to the degree of harm they have inflicted on victims. However, addressing the direct damage done against the victim(s), restoring parties’ relationships and reintegration into the community are often neglected. This paper examines alternative dispute resolution platforms and their application in the settlement of criminal matters, specifying the principle of restorative justice. This paper explored secondary methods of data collection. The libertarian theory of right guides the discussions in this paper. It is argued that ADR platforms are suitable and exhibit timely settlement of criminal matters. The parties’ satisfaction, cost cuts and avoidance of human rights violations are achievable. This article concludes that from the perspective of restorative justice, ADRs guarantee the inherent values of penitence, forgiveness and reconciliation. It is recommended that alternative dispute resolution processes be involved and given legal support in the settlement of criminal matters. Awareness and training are needed for general adoption and seamless ADR processes within the judicial system of Nigeria.